نظرات في روايات تحريف القرآن الكريم في كتاب أصول الكافي للكليني - Abdul Rahim Sulhan, Abdullah; Elatrash, Radwan Jamal Yousef (Minia University, Egypt, 2024)
تناولت هذه الدراسة التعريف بكتاب الكافي وصاحبه وبيان منزلة الكتاب وأهميته عند الشيعة الإمامية، وسلطة الدراسة الضوء على قضية تحريف القرآن الكريم عند الكليني من خلال كتابه أصول الكافي، مرتكزة على ضرب الأمثلة والشواهد القرآنية المحرفة ال واردة في كتاب أصول الكافي، والتي تدل صراحة على قصد التحريف للكتاب العزيز، واستنبطت الدراسة الهدف من وراء تحريف الكليني كما يظهر من جميع الشواهد التي تم الاستشهاد بها، بكون الدافع لذلك هو الاستدلال على معتقدهم الفاسد حول الإمامة العظمى والنص على علي وذريته، وتكمن أهمية الدراسة في كونها تسلط الضوء على مذهب منتشر في عصرنا الحالي في كثير من بلاد المسلمين لبيان موقف علماءه وأكابرهم من أعظم كتاب لدى المسلمين القرآن الكريم. ***** This study tackled the introducing of the book Al-Kafi and its author and explained the status of the book and its importance among the Imāmiyya Shi'ites. Morover the study sheds light on the issue of the alteration of the Holy Qur’an according to Al-Kulayni through his book Usul Al-Kafi, based on presenting the distorted Qur’anic examples and evidence contained in the book Usul Al-Kafi, which explicitly indicate the intention of distortion of the exalted book, the study deduced the goal behind Al-Kulayni’s distortion, as appears from all the evidence that was cited, as the motive for this was to infer their corrupt belief about the Great Imamate and the provision of Ali and his descendants. The importance of the study lies in the fact that it sheds light on a doctrine that is quite widespread in our current era in Many Muslim countries ,and the need to clarify the position of their scholars and eminent sinors regarding the greatest book among Muslims, the Holy Qur’an.